Présences, revenances et rejeux espagnols dans l’internationalisme combattant féminin au Rojava (2014-2018) - Édouard Sill (Cahiers d’histoire)
This contribution will question the international mobilization for the actual Syrian Kurdistan through the re-use, traces and frames of reference from the Spanish Civil War, both as meaning and as horizon, that is to say the “cultural transfer”. This "Hispanicization" of the syrian conflict, proceed by observers but also by some protagonists, can be observed on several scales. Considering the only dimension of the military volunteering of Western women as an operational comparison point between both conflicts, we can observe their similarities and divergences in order to identify the overlays and to consider this female-fighting internationalism as a topic in itself.